Willingness to Pay and the Distribution of Risk and Wealth - Pratt, John W.; Zeckhauser, Richard J. (Journal of Political Economy, 1996)
Willingness to pay (WTP), most economists believe, is an appropriate benefits metric for government expenditure and regulatory policies that reduce risks to human life. It depends, however, on the distribution of risk and wealth. Currently, society's expenditures overemphasize concentrated risks, say after-the-fact treatment as opposed to prevention. A "dead-anyway" effect complements excess attention to intense interests in explaining this. Our normative criterion for spending on risk reduction is what a rational, albeit uninsured, individual confronting lotteries on future risks to life and wealth would choose for himself. This requires correcting WTP to eliminate the dead-anyway effect but continues to reflect that wealth enhances the utility of living.